A 360-Degree Evaluation of Faculty Members' Teaching Effectiveness in Larestan Medical Sciences School during Covid -19 Pandemic: A Pilot Study - Maliheh Poorkiani; Nasrin Shokrpour; Zohreh Faramarzian; leila bazrafcan; Zahra Keshtkaran; Leila Bazrafkan (Shiraz University of Medical Sciences, 2023)
Background: Faculty members are the main pillars of universities, and their performance has a vital role in the efficiency of universities. In the current era of the Covid-19 pandemic, students' traditional evaluation method is not sufficient, and 360-degree evaluation is recommended, or multi-rater feedback is a means of providing evaluation from various stakeholders. The aim of this study was to compare the evaluation of faculty members' teaching effectiveness in Larestan Medical School by 360 degrees and the evaluation done by the students in 2020 during the Covid-19 pandemic.Methods: This descriptive-analytic study compared the 360 degree evaluation and the students' ratings on faculty members' performance at Larestan University of Medical Sciences during 2020 -2021. The statistical population consisted of all full-time professors (N=28) selected by census method and students (N=280) chosen by random cluster sampling. The materials used were six valid and reliable questionnaires filled out by students, an expert in evaluation, heads of departments, deputies, peers, and self-assessment of faculty members. Data were analyzed through SPSS software (version 23) using the Friedman test (P<0.001).Results: The results showed a significant difference between the 360-degree evaluation and students' ratings (P=0.05). According to the students' attitudes, there was a significant difference between the mean scores of the faculty members' communication skills and instructional skills (P<0.001). In addition, according to the head of departments, peers, an expert in the evaluation and self-assessment of faculty members, there was a positive and significant correlation between these two evaluations. However, there was no correlation between the heads of departments' views and those of the deputies for education (P<0.001).Conclusion: Given the views of different participants in this study and the dimensions of assessment of faculty members, it seems that 360-degree assessment is more realistic and fair to be done in universities. In general, it is suggested that professors, in order to better understand their strengths and weaknesses, should pay more attention to all stakeholders' views in 360-degree evaluation to improve the quantity and quality of education.